Effects of Relationship Quality on Citizen Intention Use of E-government Services: An Empirical Study of E-government System - Berlilana Berlilana; Taqwa Hariguna; Min Tsai Lai (Institute of Advanced Engineering and Science, 2018)
This study aims to explain the concept of relationship quality on citizen intention use of e-Government service. We have built 5 hypotheses. The result of 5 hypotheses is positive and significant impact. In building citizen relationship, we build two antecedent they are perceived e-Government usability and perceived e-Government credibility. The method we use in this research is empirical, with 366 valid respondents.